Kinerja Operasi Bus Eksekutif dan Travel Rute Bandar Lampung - Bandung. - Dwi Herianto; Syukur Sebayang; Arengga Vinata (UNIVERSITAS LAMPUNG, 2013)
This study was conducted in order to know service level of excutive bus and travel car and also tofind user transport characteristic in choosing modes of transportation and get a modal choice ofmode which explain probability of user transport in mode choice executive bus and travel carroute Bandar Lampung – Bandung. In this study the method uses is ducle linear regression analy-sis to look for utility of executive bus and travel car be based on movement plan of work/officialaffair, social visit, school/lecture, and recreation. From this value of utility we can calculateprobability of mode choice executive bus and travel car.Research product indicate that the highest probability value of mode choice be based on move-ment plan of work/official affair with Damri executive bus is 41%, movement plan of social visitwith Damri executive bus is 46%, movement plan of school/lecture with Kramat Djati executivebus is 59% and than movement plan of recreation with Damri executive bus is 61%.